Ski‐related novel protein suppresses the development of diabetic nephropathy by modulating transforming growth factor‐β signaling and microRNA‐21 expression. Issue 10 (7th March 2019) - Wang, Yuanyuan; Liu, Lingling; Peng, Wei; Liu, Huiming; Liang, Luqun; Zhang, Xiaohuan; Mao, Yanwen; Zhou, Xingcheng; Shi, Mingjun; Xiao, Ying; Zhang, Fan; Zhang, Yingying; et al.
Abstract: Unveiling the mechanisms that drive the pathological phenotypes of diabetic nephropathy (DN) could help develop new effective therapeutics for this ailment. Transforming growth factor‐β1 (TGF‐β1)/Smad3 signaling is aberrantly induced in DN, leading to elevated microRNA‐21 (miR‐21) expression and tissue fibrosis. Ski‐related novel protein (SnoN) negatively regulates the TGF‐β pathway, but the relationship between SnoN and miR‐21 has not been described in the context of DN. In this study, this association was investigated in vivo (streptozotocin‐induced rat model of diabetes) and in vitro (NRK‐52E model system under high glucose conditions). In both model systems, we observed reduced amounts of the SnoN protein and elevated miR‐21 amounts, indicative of an inverse relationship. These changes in SnoN and miR‐21 amounts were accompanied by reduced E‐cadherin and elevated α‐smooth muscle actin and collagen III levels, consistent with epithelial to mesenchymal transition (EMT). In vitro overexpression of SnoN in NRK‐52E cells downregulated miR‐21 at the transcriptional and posttranscriptional levels and repressed EMT and extracellular matrix (ECM) deposition. In contrast, knockdown of SnoN resulted in miR‐21 upregulation, particularly at the transcriptional level. We further demonstrated that overexpression and inhibition of miR‐21 promoted and suppressed EMT and ECM deposition, respectively, without affecting SnoN levels. Our results indicated that SnoN suppresses the development of DN as well as renal fibrosis by downregulating miR‐21, and therefore represents a novel and promising therapeutic target for DN. Abstract : Our results indicated that Ski‐related novel protein (SnoN) suppresses the development of diabetic nephropathy (DN) as well as renal fibrosis by downregulating microRNA‐21 (miR‐21), and therefore represents a novel and promising therapeutic target for DN.